Shared genomic outliers across two divergent population clusters of a highly threatened seagrass - Nikki Leanne Phair; Robert John Toonen; Ingrid Knapp; Sophie von der Heyden (PeerJ, 2019)
The seagrass, Zostera capensis, occurs across a broad stretch of coastline and wide environmental gradients in estuaries and sheltered bays in southern and eastern Africa. Throughout its distribution, habitats are highly threatened and poorly protected, increasing the urgency of assessing the genomic variability of this keystone species. A pooled genomic approach was employed to obtain SNP data and examine neutral genomic variation and to identify potential outlier loci to assess differentiation across 12 populations across the ∼9,600 km distribution of Z. capensis. Results indicate high clonality and low genomic diversity within meadows, which combined with poor protection throughout its range, increases the vulnerability of this seagrass to further declines or local extinction. Shared variation at outlier loci potentially indicates local adaptation to temperature and precipitation gradients, with Isolation-by-Environment significantly contributing towards shaping spatial variation in Z. capensis. Our results indicate the presence of two population clusters, broadly corresponding to populations on the west and east coasts, with the two lineages shaped only by frequency differences of outlier loci. Notably, ensemble modelling of suitable seagrass habitat provides evidence that the clusters are linked to historical climate refugia around the Last Glacial Maxi-mum. Our work suggests a complex evolutionary history of Z. capensis in southern and eastern Africa that will require more effective protection in order to safeguard this important ecosystem engineer into the future.